ACACIA GLOMEROSA AND ENTEROLOBIUM CYCLOCARPUM GUM EXUDATES: FUNGÍ CULTURE SUBSTRATE - L Mesa C; S Rodríguez V; M Romero; G Semprum; G León R (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2000)
The behavior of fungi species Sincephalastrum racemosam, Monoascus ruber and Trichophyton mentagmphytes on a substrate prepared with a mixture of Acacia glomerosa and Enterolobium cyclocarpum exudates was assessed. These native polymers are constituted by galactose, arabinose, rhamnose, uronic acid and proteins, presenting nitrogen, calcium and magnesium as trace elements. Colony morphology and laminate culture studies were made. Micromorphological characteristics of each of these fungi species were unmistakably observed in the gum substrate; these were comparable to those observed in the reference culture: dried leaves of Canna generalis. The growth and development of S. racemosum, M. ruber and T. mentagrophytes in the gum exudate mixture may be related to the enzymatic ability of these fungi to use the carbón source of the polymers. The results obtained confirm the benefits of the gum exudate substrate as an ideal culture medium for the identification of fungi. This fact may have economical implications since these substrates may begin to compete with traditional cultures